EFFECT OF AGE ON SEMINAL CHARACTERISTICS OF JERSEY BULL SEMEN - BHATT, P; TIWARI, R P; JAISWAL, V K (The Indian Journal of Animal Reproduction, 2016)
Sixty ejaculates each from young (2.5-3 yr, n=5) and old (6-8 yr, n=5) Jersey bulls were evaluated for fresh andpost thaw semen characteristics. The old bulls had higher (p0.05) between young and old bulls. In brief, age has no predominant impact on seminalcharacteristics of Jersey bull semen
Keywords: Age; Jersey bull; Post thaw; Semen; Spermatozoa